Oyster Cultivation Betting on Foreign Workers: A Study of Indonesian Workers in Hiroshima - Muhammad Reza Rustam (Universitas Diponegoro, 2021)
One of the reasons foreign workers are looking for jobs abroad is that there are not enough jobs in their home countries. Indonesia is one of the countries that send migrant workers to more developed Asian and Middle Eastern countries. The increasingly rapid flow of globalization in the world goes together with the need for new workers to fill the industry, especially in Japan. This condition has forced Japan to open doors for foreign workers from developing countries to satisfy demand. These workers usually come from developing countries, such as Indonesia, Vietnam, China, the Philippines, and others. In general, they occupy the less desirable working positions over Japanese youth, the so-called 3D work (dirty, dangerous, and demanding). Therefore, the current dynamics of these migrant workers' life in Japan becomes an exciting subject to comprehend, especially for the Indonesian migrant workers. This study aims to determine the dynamics of Indonesian worker's life while working in the Japanese fisheries sector. In particular, the study looks at those who work in oyster cultivation in Hiroshima prefecture. This research was carried out using descriptive analysis methods and field study with in-depth interviews conducted from 2016-2018. The interviews performed in this study were structured to find answers for the following questions: What problems do the workers face while living in Japan? What kind of processes did they go through before coming to Japan? While working in the Japanese fishing industry, how was their life as a Muslim minority?